RELIABILITY ANALYSIS AND OPTIMIZATION DESIGN OF THE SHEARER’S TORQUE SHAFT - ZHAO LiJuan; LI MingHao; ZHANG PinHao (Jixie qiangdu)
As the protection of key component of the Shearer,torque shaft has a significant impact on the performance of the reliability and fatigue life of the shearer. Shearer’s flexible virtual prototype coupling model of torque shaft,rocker arm shell,planet shafts and carrier was established,combined with the actual working condition,pro-and post drums ’ load files were obtained. Based on the " shearer’s load simulation program ",shear stress and strain contours of the torque shaft were obtained by ADAMS. Based on neural network and reliability sensitivity theory,the torque shaft shear stress and strain ’s sensitivity of unloading groove structure parameters were obtained. To shearer traction speed and torque shaft shear stress and displacement as constraints,optimize the unloading groove. Results show that when the shearer traction speed is greater than 12. 2367m/min,the torque shaft fracture in time,could improve the reliability of coal winning machine and service life.